House sparrow biomarkers as lead pollution bioindicators: Evaluation of dose and exposition length on hematological and oxidative stress parameters - Cid, Fabricio Damian (2018)
House sparrows (Passer domesticus) have been proposed as a key ecological indicator of urban pollution. Remarkably, we lack knowledge about the physiological effects of lead on this bird species. Therefore, this study was aimed to evaluate the effect of Pb on several physiological parameters in house sparrows exposed to environmental Pb concentrations. In a first experiment, birds were exposed to Pb sub-lethal doses (from 1.3 to 14.0 µg of Pb/g animal/day) during 5 days, which resulted in a dose response increase of blood Pb levels and decrease of blood ALAD activity. However, at the higher doses tested (> 7 μg of Pb/g animal/day) the blood ALAD activity inhibition (~82%) remained constant. Hematocrit and hemoglobin were significantly reduced only at the highest-doses, and the stress indicator, heterophils to lymphocyte (H/L) ratio, did not show apparent changes. In a second experiment, house sparrows were exposed to Pb in drinking water (12.3 ppm) during either 15 or 30 days. Pb concentration used in this study was enough to produce blood lead levels equivalents to those found recently in house sparrows inhabiting urban areas, reduced blood ALAD activity and inversion of the H/L ratio. Decreasing blood ALAD activities were correlated with increasing blood Pb levels. In addition, Pb exposure produced modification in the levels of hepatic antioxidant enzymes, increased GST activity and decreased CAT activity, without lipid peroxidation. In conclusion, our results suggest that blood ALAD activity is a reliable and sensitive biomarker for environmental Pb exposure in house sparrows, additionally chronic exposure produce physiological stress (H/L inversion) and small changes in antioxidant enzyme activity. Finally, this specie could be considered a bioindicator for monitoring the urban Pb contamination.